A potential industrial waste–waste synchronous treatment scheme of utilizing copper slag flotation tailings to remediate Cr(VI)-containing wastewater. Issue 3 (June 2022) - Zhai, Qilin; Liu, Runqing; Wang, Changtao; Jing, Nianwen; Xie, Feifei; Wen, Xiaofei; Sun, Wei
Abstract: Untreated Cr(VI)-containing wastewater and long-term stockpiled copper slag flotation tailings (CSTs) cause massive irreversible soil and water pollution. The current study explored an environmentally friendly method for aqueous Cr(VI) remediation using CST, which was improved by reduction calcination with anthracite as the reductant. X-ray diffraction (XRD), Fourier infrared (FTIR), and scanning electron microscopy (SEM) coupled with energy-dispersive spectrometry (EDS) indicated that reduction calcination could promote the transformation of fayalite to zero-valent iron (Fe 0 ), which is beneficial to enhance the reduction ability of CST for Cr(VI). The CST calcined with 20% anthracite at 1300 °C for 40 min had the best Cr(VI) remediation performance. Compared with raw CST without Cr(VI) remediation ability, anthracite-calcined CST (ACST) can achieve 100% Cr(VI) remediation efficiency. Moreover, ACST exhibited excellent removal capacity for As(III), Pb(II), and Cd(II). Multi-characterizations supported that the Fe 0 in ACST provides electrons to promote the reduction of Cr(VI) to Cr(III), and then Cr(III) was deposited on the surface of Fe 0 in the form of hydroxide precipitation. The remediation mechanism could be attributed to the joint contribution of reduction, precipitation, and coprecipitation. The present study provides new insights into the remediation of Cr(VI)-containing wastewater and the reuse of CST. Graphical Abstract: ga1 Highlights: Anthracite calcination improved the Cr(VI) remediation performance of Cu slag. Cr(VI) was effectively removed from wastewater by modified Cu slag. Cr(VI) are deposited on Fe 0 surfaces in the form of hydroxide precipitation. Reduction, precipitation, and coprecipitation are the mechanisms of Cr(VI) removal. Cu slag use in wastewater treatment brings double environmental benefits.